Nanoscale partitioning of Mn between austenite and martensite revealed by Curie temperature variations. (1st February 2018) - Dastur, P.; Zarei-Hanzaki, A.; Rahimi, R.; Klemm, V.; De Cooman, B. C.; Mola, J.
Abstract: The partitioning of Mn between deformation-induced martensite and austenite phases of a Fe−18Mn−2Al−2Si−0.04C high-Mn steel was studied by tracking variations in the Curie temperature of martensite after exposure to successively higher annealing temperatures. The increase in Curie temperature was justified by the Mn depletion of martensite. Assuming a linear relationship between the Curie temperature and Mn concentration, the average Mn concentration of martensite was expressed as a function of annealing temperature. The proposed method, which is applicable in a dilatometer with inductive heating, enables the ready estimation of Mn partitioning in intercritically annealed medium- and high-Mn steels.